Long‐Term Doppler Hemodynamics and Effective Orifice Areas of Edwards SAPIEN and Medtronic CoreValve Prostheses after TAVI. Issue 3 (24th September 2013) - Spethmann, Sebastian; Dreger, Henryk; Baldenhofer, Gerd; Pflug, Eyleen; Sanad, Wasiem; Stangl, Verena; Baumann, Gert; Grubitzsch, Herko; Sander, Michael; Stangl, Karl; Laule, Michael; Knebel, Fabian
<x xml:space="preserve">Abstract</x> Background Although initial hemodynamics of percutaneously implanted aortic bioprostheses compare favorably to surgically implanted valves, the durability of the flow characteristics remains unknown. As biological prostheses are at potential risk for early degeneration, the aim of our study was to compare Doppler hemodynamics and effective orifice area (EOA) directly after and at least 1 year after valve implantation. Methods In this monocentric, prospective study, we determined peak velocity, peak and mean systolic gradients, and EOA by echocardiography in 75 patients (Edwards SAPIEN, n = 20; CoreValve, n = 55) 1 week (median 7 ± 25 days) and 1 year (median 378 ± 157 days, maximum 1034 days) after transcatheter aortic valve implantation (TAVI). Results After 12 months, Doppler performance of the aortic valve prostheses remained unchanged. The peak instantaneous velocity was 1.9 ± 0.4 m/s directly after TAVI versus 1.8 ± 0.5 m/s (P = ns) at follow‐up, with a mean gradient of 8.5 ± 3.7 mmHg and 8.1 ± 4.2 (P = ns), respectively. Interestingly, the degree of mitral regurgitation (MR) decreased significantly (P = 0.007) over time, and the severity of aortic regurgitation (AR) remained unchanged during follow‐up (P = ns). Conclusion For at least 1 year after TAVI, the excellent Doppler hemodynamics and EOA are preserved in transcatheter aortic valve prostheses, and the severity of MR decreased significantly. In addition, we found no evidence of early valve deterioration or progression of AR.